Genome Characterization of the First Mimiviruses of Lineage C Isolated in Brazil - Assis, Felipe L.; Franco-Luiz, Ana P. M.; Santos, Raíssa N. dos; Campos, Fabrício S.; Dornas, Fábio P.; Borato, Paulo V. M.; Franco, Ana C.; Abrahao, Jônatas S.; Colson, Philippe; Scola, Bernard La (Frontiers in Microbiology, 2017)
The family Mimiviridae, comprised by giant DNA viruses, has been increasingly studied since the isolation of the Acanthamoeba polyphaga mimivirus (APMV), in 2003. In this work, we describe the genome analysis of two new mimiviruses, each isolated from a distinct Brazilian environment. Furthermore, for the first time, we are reporting the genomic characterization of mimiviruses of group C in Brazil (Br-mimiC), where a predominance of mimiviruses from group A has been previously reported. The genomes of the Br-mimiC isolates Mimivirus gilmour (MVGM) and Mimivirus golden (MVGD) are composed of double-stranded DNA molecules of ~1.2 MB, each encoding more than 1,100 open reading frames (ORFs). Genome functional annotations highlighted the presence of mimivirus group C hallmark genes, such as the set of seven aminoacyl-tRNA synthetases. However, the set of tRNA encoded by the Br-mimiC was distinct from those of other group C mimiviruses. Differences could also be observed in a genome synteny analysis, which demonstrated the presence of inversions and loci translocations at both extremities of Br-mimiC genomes. Both phylogenetic and phyletic analyses corroborate previous results, undoubtedly grouping the new Brazilian isolates into mimivirus group C. Finally, an updated pan-genome analysis of genus Mimivirus was performed including all new genomes available until the present moment. This last analysis showed a slight increase in the number of clusters of orthologous groups of proteins among mimiviruses of group A, with a larger increase after addition of sequences from mimiviruses of group B and C, as well as a plateau tendency after the inclusion of the last four mimiviruses of group C, including the Br-mimiC isolates. Future prospective studies will help us to understand the genetic diversity among mimiviruses.